The practice and law of banking - Sheldon, Herbert Percival; Drover, C.B. (London : Macdonald and Evans, 1958)
The object of this book is to provide, for the practical bank man and for the student of English banking law and practice, a manual sufficiently extensive in scope to meet present day requirements. This edition includes the changes brought about by the Cheques Acts, 1957.
With the text of the Bills of exchange act, 1882; the Bills of exchange (time of noting) act, 1917; Cheques act, 1957; the Agricultural Credits act, 1928; and extracts from solicitors' accounts and trust accounts rules, 1957; and legislation and controls affecting Banks.
Includes index.
Includes bibliographical references: p. 551-552.
occ 18/01/2019
Loans
Keywords: Banking law; Banks and banking